The role of higher education in development of entrepreneurial competencies: Some insights from Castilla-La Mancha University in Spain - Ángela González Moreno; Llanos López Mu\~noz; Rosario Pérez Morote (Administrative Sciences, 2019)
This study presents an analysis of the entrepreneurial competences of second- and fourth-year undergraduate students at the University of Castilla-La Mancha (UCLM), under the framework of the Entrepreneurial Teachers Network, an ongoing project at this institution. The analysis of a sample of 1874 students identified three profiles of competences of students at the UCLM. The first profile is related to competences in performing and resolving activities, the second is related to risk aversion and uncertainty management and the third is associated with the capacity for teamwork. Furthermore, it was found that the competences related to implementing and performing activities significantly influence job creation as they exhibit a positive relationship with the intention of creating a company in the first three years after graduation. Emotion-related competences also exhibit a significant effect on entrepreneurial intention, although this association is negative. Finally, relation-based competences were found to have no impact on entrepreneurial intention.
Keywords: 350; entrepreneurship; entrepreneurship education; entrepreneurial teachers; cross-curricular competences; job creation; entrepreneurial competencies; entrepreneurial university